2004
DOI: 10.1074/jbc.m405911200
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Dynamics of EBNA1-oriP Interaction during Latent and Lytic Replication of Epstein-Barr Virus

Abstract: The Epstein-Barr virus (EBV) nuclear antigen 1 (EBNA1) is required for maintenance of the viral genome DNA during the latent phase of EBV replication but continues to be synthesized after the induction of viral productive replication. An EBV genome-wide chromatin immunoprecipitation assay revealed that EBNA1 constantly binds to oriP of the EBV genome during not only latent but also lytic infection. Although the total levels of EBNA1 proved constant throughout the latter, the levels of the oriP-bound form were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
4
25
1
Order By: Relevance
“…Immunofluorescence analysis with an anti-HA antibody revealed that HA-tagged EBNA1 localized to discrete, intranuclear punctate dots, which colocalized with FISH signals of EBV genomes. This punctate localization pattern of EBNA1 corresponded well with the localization of EBNA1 observed in latently infected B95-8 cells (Daikoku et al, 2004). Others have observed a diffuse pattern of EBNA1 localization (in interphase nuclei or on mitotic chromosomes) in other latently infected cells (Petti et al, 1990), and in cells overexpressing EBNA1 (Hung et al, 2001;Ito et al, 2002;Kanda et al, 2001a;Marechal et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…Immunofluorescence analysis with an anti-HA antibody revealed that HA-tagged EBNA1 localized to discrete, intranuclear punctate dots, which colocalized with FISH signals of EBV genomes. This punctate localization pattern of EBNA1 corresponded well with the localization of EBNA1 observed in latently infected B95-8 cells (Daikoku et al, 2004). Others have observed a diffuse pattern of EBNA1 localization (in interphase nuclei or on mitotic chromosomes) in other latently infected cells (Petti et al, 1990), and in cells overexpressing EBNA1 (Hung et al, 2001;Ito et al, 2002;Kanda et al, 2001a;Marechal et al, 1999).…”
Section: Discussionsupporting
confidence: 73%
“…Using biochemical fractionation, Kanda and colleagues (Kanda et al, 2001) observed that EBNA1 from interphase cells sedimented with the chromosomal pellet and was released by micrococcal nuclease, which is consistent with interaction of EBNA1 with chromosomes in interphase. By contrast, biochemical fractionation approaches used by Daikoku, Ritzi and colleagues (Daikoku et al, 2004;Ritzi et al, 2003) found little EBNA1 from interphase cells in the chromosomal pellet. Such divergent results might be due to the different buffer conditions used in each study.…”
Section: Discussionmentioning
confidence: 88%
“…For example, biochemical fractionation performed by Kanda and coworkers (Kanda et al, 2001) support the conclusion that EBNA1 is bound to chromatin, whereas those performed by Daikoku and colleagues (Daikoku et al, 2004) indicate that EBNA1 is largely soluble. However, these experiments were performed using different buffer conditions (salt and detergent concentrations), which might account for this discrepancy.…”
Section: Is Ebna1 Associated With Chromatin In Interphase?mentioning
confidence: 98%
See 2 more Smart Citations